WISATA RAMAH MUSLIM PULAU BERPENGHUNI DI KEPULAUAN SERIBU: ANALISIS DENGAN METODE ANALYTIC NETWORK PROCESS (ANP) - Nursyahid, M; Haryanti, Ely; Arnoldy, Arnoldy (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2024)
This study analyzes the readiness level of Muslim-friendly tourism in the inhabited islands of the Thousand Islands using the Analytic Network Process (ANP) method. The focus of the research is on 11 inhabited islands with tourism potential, considering various halal tourism criteria according to the Global Muslim Travel Index (GMTI) standards. The analysis was conducted through field surveys, stakeholder interviews, and documentary studies during the period of January-June 2024. The results show that the priority development sequence based on the ANP supermatrix is as follows: worship facilities, services, access, environment, and communication. Evaluations of key islands such as Tidung, Pramuka, Panggang, Kelapa, and Harapan reveal variations in the readiness of Muslim-friendly facilities and services. A SWOT analysis identifies key strengths, including the Muslim-majority population and the availability of mosques, while major weaknesses include limited infrastructure and a lack of halal certification. Development opportunities are supported by the global halal tourism trend and government support, but face threats from competition with other destinations and the impact of climate change. The study recommends a three-stage development strategy: short-term (facility mapping and basic training), medium-term (infrastructure development and halal certification), and long-term (integration with national halal tourism destinations and branding enhancement). Research limitations include access to secondary data, seasonal variations in visits, and dynamic policy changes.